2008
DOI: 10.1007/s00249-008-0258-3
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid interdigitation in stratum corneum model membranes: a neutron diffraction study

Abstract: The influence of the chain length of the free fatty acid (FFA) in a stratum corneum (SC) lipid model membrane composed of N-(alpha-hydroxyoctadecanoyl)-phytosphingosine (CER [AP]), cholesterol (Ch), FFA and cholesterol sulphate (ChS) was investigated by neutron diffraction. The internal nanostructure of the SC lipid membrane in addition to the water distribution function was determined via calculation of the neutron scattering length density profile (Fourier profile). The Fourier profiles of the studied SC mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 48 publications
0
48
0
Order By: Relevance
“…Subtraction of the SLD curves is performed in reciprocal space, and a large number of structure factors (large h max ) in eq 5 is required to accurately represent a smooth Gaussian distribution function in real space, much more than is typically measured. This leads to a truncation in the Fourier series which manifests itself in undulations around the central peak of the distribution, like what was seen and discussed recently by Ruettinger et al (32). Thus when we fit a Gaussian distribution function to the difference profile, since fitting is also performed in reciprocal space directly on the measured structure factors (33,34), we focus on only the central peak.…”
Section: Resultsmentioning
confidence: 99%
“…Subtraction of the SLD curves is performed in reciprocal space, and a large number of structure factors (large h max ) in eq 5 is required to accurately represent a smooth Gaussian distribution function in real space, much more than is typically measured. This leads to a truncation in the Fourier series which manifests itself in undulations around the central peak of the distribution, like what was seen and discussed recently by Ruettinger et al (32). Thus when we fit a Gaussian distribution function to the difference profile, since fitting is also performed in reciprocal space directly on the measured structure factors (33,34), we focus on only the central peak.…”
Section: Resultsmentioning
confidence: 99%
“…The latter has been extensively studied and described before [12,13,25]. It was shown that the driving force for the highly ordered nanostructure of the CER[AP]-based model membrane is the ceramide itself [13], and that the lamellar repeat distance remains stable even if the fatty acid is replaced by long-chain species [26]. Probably due to strong hydrogen bonds formed between the head groups of the CER molecules, a framework with a high state of lamellar order is built, and the other membrane components such as PA, CHOL and ChS are forced to arrange themselves inside the bilayers of short repeat distance of about 46 Å.…”
Section: Resultsmentioning
confidence: 99%
“…VLCFAs are also abundant in sphingolipids in animal cells. It has been proposed that the lipid bilayer organization of the stratum corneum could be stabilized by a partial interdigitation between the two leaflets (Ruettinger et al, 2008). Interdigitation of long-chain fatty acid residues between complex lipids might thus represent a common feature in plants and animals that allows a higher thermal stability of the outer leaflet, as described in artificial asymmetrical liposomes prepared with animal lipids (Cheng et al, 2009).…”
Section: Saturated Vlcfas Of Gipcs Interdigitate the Two Leafletsmentioning
confidence: 99%